SomethiNG 2 talk about-Transcriptional regulation in embryonic and adult oligodendrocyte precursors - Küspert, Melanie; Wegner, Michael (Brain Research, 2016)
Glial cells that express the chondroitin sulfate proteoglycan NG2 represent an inherently heterogeneous population. These so-called NG2-glia are present during development and in the adult CNS, where they are referred to as embryonic oligodendrocyte precursors and adult NG2-glia, respectively. They give rise to myelinating oligodendrocytes at all times of life. Over the years much has been learnt about the transcriptional network in embryonic oligodendrocyte precursors, and several transcription factors from the HLH, HMG-domain, zinc finger and homeodomain protein families have been identified as main constituents. Much less is known about the corresponding network in adult NG2-glia. Here we summarize and discuss current knowledge on functions of each of these transcription factor families in NG2-glia, and where possible compare transcriptional regulation in embryonic oligodendrocyte precursors and adult NG2-glia. This article is part of a Special Issue entitled SI:NG2-glia (Invited only).
EVALuna2:4984